f-statistical convergence of order ? for sequences of fuzzy numbers - Altinok, Hifsi; Kasap, Mithat (Ios Press, 2017)
In this paper, we extend the notions of statistically convergence of order beta and strong Cesaro summability of order beta, and introduce the notions f-statistically convergence of order beta and strong Cesaro summability of order beta for beta is an element of (0, 1] with respect to an unbounded modulus function f for sequences of fuzzy numbers and give some inclusion theorems.
Keywords: Fuzzy number; sequence of fuzzy numbers; statistical convergence; Cesaro summability; modulus function